Russian Nationalism Imaginaries, Doctrines, and Political Battlefields - Laruelle, Marlene (Taylor & Francis, 2019)
This book, by one of the foremost authorities on the subject, explores the complex nature of Russian nationalism. It examines nationalism as a multilayered and multifaceted repertoire displayed by a myriad of actors. It considers nationalism as various concepts and ideas emphasizing Russia's distinctive national character, based on the country's geography, history, Orthodoxy, and Soviet technological advances. It analyzes the ideologies of Russia's ultra-nationalist and far-right groups, explores the use of nationalism in the conflict with Ukraine and the annexation of Crimea, and discusses how Putin's political opponents, including Alexei Navalny, make use of nationalism. Overall the book provides a rich analysis of a key force which is profoundly affecting political and societal developments both inside Russia and beyond.